THE EFFECTS OF GRANTS CUTS ON PUBLIC DEFICIT - DOES INCUMBENT'S IDEOLOGY MATTER? - Santiago Lago-Pe\~nas (European Regional Science Association (ERSA), 2005)
In this paper causality between taxes and expenditures is reexamined, suggesting that electoral cycle may be a relevant explicative factor. Using a data set from a wide sample of Spanish municipalities, I test if causal relationships between budgetary variables is effectively affected by the electoral cycle.
Keywords: 330